The landscape of COVID-19 vaccination among healthcare workers at the first round of COVID-19 vaccination in China: willingness, acceptance and self-reported adverse effects - Xinxin Ye; Wan Ye; Jinyue Yu; Yuzhen Gao; Ziyang Ren; Lanzhen Chen; Ao Dong; Qian Yi; Chenju Zhan; Yanni Lin; Yangxin Wang; Simin Huang; et al. (Taylor & Francis Group, 2021)
The COVID-19 vaccines have been developed in a wide range of countries. This study aimed to examine factors that related to vaccination rates and willingness to be vaccinated against COVID-19 among Chinese healthcare workers (HCWs). From 3rd February to 18th February, 2021, an online cross-sectional survey was conducted among HCWs to investigate factors associated with the acceptance and willingness of COVID-19 vaccination. Sociodemographic characteristics and the acceptance of COVID-19 vaccination among Chinese HCWs were evaluated. A total of 2156 HCWs from 21 provinces in China responded to this survey (effective rate: 98.99%)), among whom 1433 (66.5%) were vaccinated with at least one dose. Higher vaccination rates were associated with older age, working as a clinician, having no personal religion, working in a fever clinic or higher hospital grade, and having received vaccine education, family history for influenza vaccination and strong familiarity with the vaccine. Willingness for vaccination was related to working in midwestern China, considerable knowledge of the vaccine, received vaccine education, and strong confidence in the vaccine. Results of this study can provide evidence for the government to improve vaccine coverage by addressing vaccine hesitancy in the COVID-19 pandemic and future public health emergencies.